THE SCALE OF RESILIENCE IN THE PEOPLE OF SURABAYA CITY - Amiroh Untsal Asad; Hafnidar Hafnidar (SEAN Institute, 2023)
Resilience is defined as the capacity of the individual to overcome adversity and survive any psychological stress. Resilience reflects the ability to bounce back and take advantage of opportunities. In the context of Surabaya's society, brand a is required to face various serious problems, such as high population density, pollution, and job competition. This urban life leads to a tendency to experience various disordersand psychological vulnerabilities. With this condition, researchers made a psychological scale to measure the level of resilience in the people of Surabaya City. This psychological scale refers to the theory of Reivich and Shatté (2006) on the construct of resilience consisting of seven dimensions, namely emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy and reaching out. A total of 38 women and 16 men (N = 54) with an age range of 17-50 years participated in this study. The research method used is the Likert scale model. The study’s results found as many as 32 items out of 44 items tested to be valid with a total item-correlation coefficient value of more than 0.300. As for the value of Cronbach's Alpha, it is calculated at 0.909. Thus, this Resilience Scale can be used in the context of the people of Surabaya City.